(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: With the advent of Misoprostol, medical termination of pregnancy in the first trimester has become a popular choice. But its indiscriminate use with inadequate doses more often results in incomplete abortion. Manual Vacuum Aspiration PLUS (MVA-PLUS) is claimed to be an effective treatment modality for incomplete abortion. The present study was intended to evaluate the effectiveness of MVA-PLUS in the treatment of incomplete abortion. Methods: This cross-sectional study was conducted in Sherpur District Hospital, Sherpur, Bangladesh. Pregnant women of 8-12 weeks of gestation receiving tablet Misoprostol by untrained personnel and presented to us with incomplete abortion were included in the study. Patients with complete abortion, ectopic pregnancy, signs of pelvic infection or sepsis were excluded from our study. MVA-Plus was done by paracervical block, analgesia and/or mild sedation and verbal reassurance. Successful outcome was defined in terms of complete evacuation of the product of conceptus. Result: The study subjects were generally young, married with low educational background. Treatment with MVA-PLUS showed that majority (98%) of the patients have had complete evacuation with minimum duration of hospital stay (1-2 days) in majority of the cases (82%). The need for blood transfusion varied from 1-2 units (76%) to more than 5 units (4%). No major complications were noted. Conclusion: Manual Vacuum Aspiration PLUS (MVA-PLUS) is highly effective in the treatment of incomplete abortion in the first trimester of pregnency with no side effect and minimum stay in the hospital. Ibrahim Card Med J 2017; 7 (1&2): 76-79